A Systematic Review and Meta-Analysis of Health Utility Estimates in Chronic Spontaneous Urticaria - Yuan, Yan; Xiao, Yi; Chen, Xiang; Li, Jie; Shen, Minxue (Frontiers in Medicine, 2020)
Background: Chronic spontaneous urticaria (CSU) is a common recurrent skin disease that adversely affect patient’s quality of life condition to treat. Economic evaluations of health care often include patient preferences for health outcomes using utilities. Objectives: The study aimed to determine pooled estimates of utility-based quality of life in patients with CSU. Methods: We conducted a systematic review, meta-analysis, and meta-regression of peer-reviewed articles and conference papers that published from database inception to 31 April 2019 that reported utility estimates in patients with CSU. Scores reported with the EQ-5D, SF-6D, SF-12, SF-36 instruments were converted to utilities using published mapping algorithms. Meta-analysis was used to calculate the pooled and meta-regression was used to examine the effects of possible factors. Results: We identified 12 studies reporting 17 utility estimates (Table1). The mean utility estimate for CSU was 0.65 (95% confidence interval (CI): 0.64–0.66); both the I2 statistics and Cochran’s Q were 0.0%. We performed subgroup analyses by utility elicitation instrument. The pooled utility estimate that converted from SF-36 or SF-12 was 0.67 (95% CI: 0.31–1.03), 0.73 (95% CI: 0.57–0.90) for EQ-5D, and 0.65 (95% CI: 0.64–0.66) for SF-6D, respectively. According to the meta-regression, higher proportion of female patients was significantly associated lower utility estimates. Conclusions: These findings provide evidence-based utility estimates to inform health-related burden analysis of CSU.